2018
DOI: 10.4102/sajhrm.v16i0.882
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of a combined approach of perceived organisational support for strengths use and deficit correction on employee outcomes

Abstract: Orientation: The positive psychology paradigm suggests a balanced focus on employee strengths and deficits. However, an overemphasis on strengths has raised questions regarding the value of a focus on strengths use, deficit improvement or a combined approach with a balanced focus on both.Research purpose: The primary objective was to examine whether perceived organisational support (POS) for strengths use, POS for deficit improvement or a combined approach would be the strongest predictor of work engagement, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
1
9
0
1
Order By: Relevance
“…Job demands-resources (JD-R) theory suggests that individuals can benefit more from the accumulation of resources (Bakker and Demerouti, 2017). As strengths use and deficit correction can be viewed as two types of personal resources (Els et al , 2018; Mahomed and Rothmann, 2019), it is reasonable to believe that when the level of deficit correction is high, employees working on strengths will experience greater positive affect and subsequently execute more innovative behaviors. Unfortunately, no prior research tested this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Job demands-resources (JD-R) theory suggests that individuals can benefit more from the accumulation of resources (Bakker and Demerouti, 2017). As strengths use and deficit correction can be viewed as two types of personal resources (Els et al , 2018; Mahomed and Rothmann, 2019), it is reasonable to believe that when the level of deficit correction is high, employees working on strengths will experience greater positive affect and subsequently execute more innovative behaviors. Unfortunately, no prior research tested this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased performance can also result from DBA (Abdullah, Ahsan, & Alam, 2009). Therefore, focusing on both strengths use and deficit correction may be beneficial for an organisation (Els, Mostert, & Van Woerkom, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mohammed et al (2019) found that POSDC, task performance, and contextual performance were positively associated. Moreover, according to Els and colleagues (Els et al, 2018), the more people engage in activities to correct their deficits, the more they tend to feel a sense of self-efficacy. However, in both studies, even if the results are significant, reported effect sizes are relatively low.…”
Section: Deficit Correction Strengths-based Approach and Performancementioning
confidence: 99%
“…However, these studies might minimize the effect that deficit correction may have on employees' holistic development. For instance, several articles have demonstrated deficit correction effectiveness on task-related performance and employee engagement (Els et al, 2018;van Woerkom et al, 2016). Therefore, the above invites the scientific community to develop one (or more) conceptual framework that integrates both the strengths-based approach and deficits correction to compare their possible positive or negative consequences on employees' optimal functioning (Bakker & van Woerkom, 2018;Miglianico et al, 2019).…”
mentioning
confidence: 99%